FAKTOR PENYEBAB KECELAKAAN LALU LINTAS: STUDI KASUS BEBERAPA JALAN DI KOTA SURABAYA - Hera Widyastuti; Adita Utami (Journal of Indonesia Road Safety, 2018)
Indonesia on the fifth ranks in the world considering of accident number, after China, India, Afghanistan, and Nigeria, where East Java is the province that has the highest accident in Indonesia. The city of Surabaya as the Capital of East Java Province automatically became the centre of government activities, giving rise to transportation activities that indirectly had an impact on accidents. Therefore, it is necessary to conduct research to obtain the accident rate and the location of black site in the city of Surabaya. In addition, considering that productive age including junior high school (SMP) is the highest contributor on the accidents, the level of understanding of junior high school students on traffic regulations needs to be analysed. From the data obtained at IRSMS, it can be seen that five roads in Surabaya were the highest contributors to accidents in Surabaya, namely Mastrip, Diponegoro, A. Yani, Kenjeran, and Ir. Soekarno, where the five roads are inter-city connecting roads that blend with the road in the city. In addition, from the interview data, there was a relationship between awareness of traffic behaviour and willingness to protect themselves. Indonesia menduduki peringkat kelima, setelah Tiongkok, India, Afghanistan, dan Nigeria. Dan Jawa Timur adalah propinsi yang mempunyai kecelakaan tertinggi di Indonesia. Kota Surabaya sebagai Ibukota Provinsi Jawa Timur secara otomatis menjadi pusat kegiatan pemerintahan, sehingga menimbulkan kegiatan transportasi yang secara tidak langsung berdampak pada terjadinya kecelakaan. Oleh karenanya perlu dilakukan penelitian untuk memperoleh nilai accident rate, serta black site di Kota Surabaya. Selain itu mengingat usia produktif termasuk anak sekolah tingakat Sekolah Menengah Atas (SMP) adalah penyumbang kecelakaan tertinggi, maka tingkat pemahaman para pelajar SMP terhadap peraturan lalu lintas perlu di analisa. Dari data yang didapat pada IRMS, terlihat bahwa lima jalan di kota Surabaya menjadi penyumbang kecelakaan tertinggi di Surabaya, yaitu jalan A. Yani, Mastrip, Diponegoro, Kenjeran dan Ir. Soekarno, dimana kelima jalan tersebut adalah jalan-jalan penghubung antar kota yang berbaur dengan jalan dalam kota. Selain itu dari data wawancara diperoleh hubungan antara niat dengan kepatuhan terhadap peraturan lalu lintas.